Fun & Reality: A Critical Discourse Analysis of Political memes on Social Media (2016–2024) - Akhlaq, Mahnoor (JELLL, 2025)
This study delves into the interaction between humor and reality in political memes circulated on social media, employing Norman Fairclough’s three-dimensional (3D) model of critical discourse analysis (CDA). As a prevalent form of expression in the digital era, political memes merge entertainment with political critique. The objective of this research is to reveal how these memes serve as discursive practices, molding and mirroring public understanding of political truths. Utilizing Fairclough’s 3D model, this study examines political memes across three dimensions: textual analysis, discursive practice, and sociocultural practice. The research utilizes a mixed-methods strategy, merging quantitative content analysis of a diverse array of political memes from different social media platforms with qualitative case studies of notably impactful or contentious memes. Results suggest that political memes function as both a source of widespread amusement and a means of political involvement, frequently simplifying intricate topics into easily digestible, amusing content that can uphold or challenge prevailing political storylines.